Public health aspects of the world’s largest mass gathering: Kumbh Mela 2019 Prayagraj Uttar Pradesh, India - Gautam, Anurag; Singh, S. K.; Mohan, Uday; Manar, Manish; Gautam, Kiran (International Journal Of Community Medicine And Public Health, 2021)
The influx of large numbers of people to mass gathering events may give rise to specific public health risks. Kumbh-Mela is internationally famous religious mass gathering. It creates the substantial challenge of creating a temporary city in which millions of pilgrims/visitors can stay for a defined period of time. The arrangements need to allow this very large number of people to reside with proper medical services, adequate supplies of food, electricity, waste disposal, clean water and transportation etc. Understanding the Kumbh-Mela can highlight the health challenges faced and provide the crucial lessons for the management of mass gatherings.